High-efficiency fungal pathogen intervention for seed protection: new utility of long-chain alkyl gallates as heat-sensitizing agents - Kim, Jong H.; Chan, Kathleen L.; Hart-Cooper, William M.; Palumbo, Jeffrey D.; Orts, William J. (Frontiers in Fungal Biology, 2023)
Control of food-contaminating fungi, especially pathogens that produce mycotoxins, is problematic since effective method for intervening fungal infection on food crops is often limited. Generally Regarded As Safe (GRAS) chemicals, such as natural compounds or their structural derivatives, can be developed as antimicrobial agents for sustainable food/crop production. This study identified that long-chain alkyl gallates, i.e., octyl-, nonyl-, and decyl gallates (OG (octyl 3,4,5-trihydroxybenzoic acid), NG, DG), can function as heat-sensitizing agents that effectively prevent fungal contamination. Out of twenty-eight candidate compounds and six conventional antifungal agents examined, the heat-sensitizing capacity was unique to the long-chain alkyl gallates, where OG exhibited the highest activity, followed by DG and NG. Since OG is a GRAS compound classified by the United States Food and Drug Administration (FDA), further in vitro antifungal studies were performed using OG. When OG and mild heat (57.5°C) were co-administered for 90 seconds, the treatment achieved > 99.999% fungal death (> 5 log reduction). Application of either treatment alone was significantly less effective at reducing fungal survival. Of note, co-application of OG (3 mM) and mild heat (50°C) for 20 minutes completely prevented the survival of aflatoxigenic Aspergillus flavus contaminating crop seeds (Brassica rapa Pekinensis), while seed germination rate was unaffected. Heat-sensitization was also determined in selected bacterial strains (Escherichia coli, Agrobacterium tumefaciens). Altogether, OG is an effective heat-sensitizing agent for control of microbial pathogens. OG-mediated heat sensitization will improve the efficacy of antimicrobial practices, achieving safe, rapid, and cost-effective pathogen control in agriculture/food industry settings.